Representações culturais das mulheres na China (1892-1934): o ensino de história a partir dos romances A boa terra e Pavilhão de mulheres, de Pearl Buck - Rodrigues, Márcio (My University, 2020)
The present work is the result of research developed in the Professional Master’s Program in History Teaching at the University of Caxias do Sul, in the area of concentration teaching history: sources and languages. Line of research: languages and culture in history teaching. Based on Roger Chartier’s theoretical framework, he presents a study of the representations in cultural practices regarding gender violence against women in China present in the novels A Boa Terra (1981) and Pavilhão de Mulheres (2009), by the American writer Pearl Buck (1892-1973). In order, therefore, to present a proposal for educational material, in the form a comic strip, that can serve as a help to Basic Education teachers interested in approaching and problematizing the teaching of women’s history from another perspective, the Oriental, in the period between 1892 and 1934.
O presente trabalho é resultado de pesquisa desenvolvida no Programa de Mestrado Profissional em Ensino de História da Universidade de Caxias do Sul, na área de concentração ensino de história: fontes e linguagens. Linha de pesquisa: linguagens e cultura no ensino de história. A partir do referencial teórico de Roger Chartier, apresenta um estudo das representações nas práticas culturais referentes a violência de gênero contra as mulheres na China presentes nos romances A Boa Terra (1981) e Pavilhão de Mulheres (2009), da escritora estadunidense Pearl Buck (1892-1973). Para, assim, apresentar uma proposta de material paradidático, no formato de história em quadrinhos, que possa servir de auxílio a professores da Educação Básica interessados pela abordagem e problematização do ensino de história das mulheres a partir de outro viés, o Oriental, no período compreendido entre 1892 e1934.
Keywords: Buck, Pearl Sydenstricker, $d 1892-1973; História - Estudo e ensino; Literatura; Mulheres - China; History Study and teaching; Literacy; Women - China